Risk factors associated with low bone mineral density in children with idiopathic scoliosis: a scoping review - Yang, Yuqi; Chen, Zhengquan; Huang, Zefan; Tao, Jing; Li, Xin; Zhou, Xuan; Du, Qing (BMC musculoskeletal disorders, 2023)
Children with idiopathic scoliosis (IS) have a high risk of osteoporosis and IS with low bone mineral density (BMD) are susceptible to curve progression. This review aims to explore the risk factors of low BMD in children with IS. Studies were retrieved from 5 databases that were published up to January 2022. Search terms are keywords in titles or abstracts, including subject headings related to "Scoliosis", "Bone Mineral Density", and "Risk Factors". Observational studies on risk factors of low BMD in children with IS were enrolled in this review. The number of studies, sample size, outcome measures, research type, endocrine, and lifestyle-related factors, gene/signal pathway, and other contents were extracted for qualitative analysis. A total of 56 studies were included in this scoping review. Thirty studies involved genetic factors that may affect BMD, including the Vitamin-D receptor gene, RANK/RANKL signal pathway, the function of mesenchymal stem cells, Runx2, Interleukin-6 (IL-6), and miR-145/β-catenin pathway. Eight studies mentioned the influence of endocrine factors on BMD, and the results showed that serum levels of IL-6, leptin and its metabolites, and ghrelin in children with IS were different from the age-matched controls. In addition, there were 18 articles on lifestyle-related factors related to low BMD in children with IS, consisting of physical activity, calcium intake, Vitamin D level, and body composition. Genetic, endocrine, and lifestyle-related factors might relate to low BMD and even osteoporosis in IS. To prevent osteoporosis, the effectiveness of regular screening for low BMD risk factors in children with IS needs to be investigated. Additionally, clear risk factors suggest strategies for bone intervention. Future studies should consider the effectiveness of calcium and vitamin D supplements and physical activity in BMD improvement.